Brain organoids for addressing COVID-19 challenge - Yu, Jin; Wang, Kailun; Zheng, Dalin (Frontiers in Neuroscience, 2022)
COVID-19 is a systemic disease involving multiple organs. Clinically, patients have symptoms of neurological damage to varying degrees, however, we do not have a clear understanding of the relationship between neurological manifestations and viral infection due to the limitations of current in vitro study models. Brain organoids, the differentiation of stem cells into tiny cell clusters under 3D culture conditions, can mimic the structure of neurodevelopmental features in different patients. The paper reviews the evolution of brain organoids, the mechanism of viral infection, the inflammatory response associated with neurological damage, detection of antiviral drugs, and combined microarray technology to affirm the status of the brain organoid models in the study of COVID-19, while continuously improving the model in combination with emerging technologies, to lay a theoretical foundation for clinical applications and academic researches.